Pengembangan Media Edukatif Materi Sifat Cahaya Pembelajaran IPAS Kelas V SD Negeri Mranggen 2 - Sari, Ayu Rifenda; Azizah, Mira; Handayani, Diana Endah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The limitations of learning media, especially on the material of the properties of light in the subject of science, cause students' learning motivation to decrease. Therefore, interesting and interactive media are needed. This study aims to develop educational learning media on the material of the properties of light for grade V elementary school students that are valid and practical. Using the Research and Development method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study collected data through interviews and questionnaires on teacher and student needs, media validation, materials, and teacher and student responses. The research sample involved students and teachers of grade V of Mranggen 2 Elementary School. The results showed that the developed learning media was valid and practical. The validation of media experts reached 96% with the criteria of